Reconstructing meaning in life: a gadamerian hermeneutic reading of Zainuddin in Hamka's tenggelamnya kapal van der wijck through logotherapy - Syawaluddin Syawaluddin; Rizka Kamelia (Journal of Counseling, Education and Society, 2026)
Previous studies of Hamka's Tenggelamnya Kapal Van der Wijck examine adat hegemony and psychological conflict, but not how identity exclusion, love, work, loss, and regret form different pathways of meaning. This study used Gadamerian hermeneutics, with logotherapy as a theory-informed interpretive horizon rather than a diagnosis. The bounded corpus was the complete 1984 edition; the unit of analysis was a context-bounded dialogue, narration, or short episode. A revision-stage verification of three documented reading cycles identified 60 candidate segments, of which 48 met the explicit inclusion rules. Meanings were tested through movement between each segment, its context, the whole plot, and operational logotherapy categories. Trustworthiness was supported through contextualized quotations, a codebook, a decision trail, reflexive memoing, and disconfirming-evidence checks. Four clusters emerged: an identity wound of nonrecognition; love as an unstable experiential value; adat as a sociocultural constraint; and literary work as creative value and self-transcendence. The central finding is asynchronous meaning reconstruction: creative values can develop while attitudinal values remain unresolved. This situates freedom within sociocultural constraints and distinguishes productivity from recovery. Counseling implications are reflective-conceptual, not evidence of intervention effectiveness.